Pengaruh Kepuasan Mahasiswa terhadap Loyalitas: Studi pada Fakultas Ekonomi dan Bisnis (FEB) Universitas Brawijaya (UB) - Nikmah, Ainun (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2015)
This study examines the link between students satisfaction and thei commitment study at Faculty of Economic and Business Brawijaya University.Â This study applied an explanatory research using 360 students as respondent. The results show certainty, empathy, reliability, responsiveness, tangible simultaneously relate to studentsâ€™ commitment. Certainty, empathy, reliability, responsiveness, tangible simultaneously also assosiated with recommendation. Certainty, empathy, reliability, responsiveness, tangible related to commitments and recommendations. Certainty is the most important variable explaining students commitment and recommendations